Proposed interior design scheme of Karangkraf bookstore and cafe for Kumpulan Karangkraf Sdn. Bhd at T20 3rd Floor 150 Ipoh Parade, Jalan Sultan Abdul Jalil 30450 Ipoh Perak Darul Ridzuan / Nur Fatihah Abd Wahab - Abd Wahab, Nur Fatihah (Faculty of Architecture, Planning and Surveying, 2011)
The project that had been chosen for this final project is to Proposed Interior Design Of Bookstore and Cafe for Karangkraf at Jalan Sultan Abdul Jalil, Ipoh Parade 30450 Ipoh Perak Darul Ridzuan. The focus of this project is to solve the issues and to accomplish all the objectives of this project. The issues of the project is because of awareness, to increase the percentage of reading population in Malaysia, especially to the youth generation that less interested in reading. And one of the objective in this project is to create a new space for a new experience for Karangkraf reader, where they can enjoy reading a book and also can find the old products in this bookstore. The purpose for this project is to open a new bookstore and cafe for Karangkraf for the first time and to exposed their product to the customer about Karangkraf in the future especially to all youth generations to learn more about Bahasa Malaysia. This project also relate with Karangkraf focus which is will always be the younger generation, especially in the magazine and novel section. It is better to target an emerging market because most of the popular section is in youth segment.